Increasing Taxpayer Compliance Through Tax Literacy, Taxpayer Awareness, and Tax Digitalization - Supriyati Supriyati; Nabila Chairunnisa (Journal of Creative Power and Ambition (JCPA), 2026)
The primary objective of every company is to maximize firm value because Taxes are the primary fiscal instrument in the State Budget (APBN), contributing significantly to the revenues needed for development and the sustainability of a nation. This study was motivated by the phenomenon of Indonesia’s declining tax ratio in the first half of 2025, which only reached 8.42 percent, a figure that is still far from the national fiscal target of 11 percent. This situation contrasts with the enormous potential of the MSME sector, which comprises 66 million business units and accounts for 61 percent of GDP, but whose tax contribution is still relatively low. The low level of tax compliance in this sector is identified as being caused not only by the tariff rate, but also by low tax literacy, administrative constraints, and challenges in the application of digital technology. The purpose of this study is to determine the effect of tax literacy, taxpayer awareness, and tax digitalization the compliance of individual taxpayers. The research method used was quantitative, with samples collected using simple random sampling from a total of 138 individual taxpayers registered at the Surabaya Wonocolo Tax Office (KPP). The data analysis technique used was the Structural Equation Modeling (SEM) method using WarpPLS 7.0 statistical software. The results showed that tax literacy had no significant effect on taxpayer compliance, while taxpayer awareness and tax digitalization had a positive and significant effect on individual taxpayer compliance.